Can New Series of Half-sandwich Lanthanum(III), Erbium(III), and Ytterbium(III) Complexes of Organometallic Ferrocenyl Schiff Base Ligands Display Biological Activities as Antibacterial and Anticancer Drugs?. Issue 6 (2nd November 2022) - G. Deghadi, Reem; Mohamed, Gehad G.
ABSTRACT: A new series of La(III), Er(III), and Yb(III) complexes were synthesized from ferrocenyl Schiff base ligands (2-(1-((8-aminonaphthalen-1-yl)imino)ethyl)cyclopenta-2, 4-dien-1-yl) (cyclopenta-2, 4-dien-1-yl)iron (L 1 ) and (2-(1-((1-carboxyethyl)imino)ethyl) cyclopenta-2, 4-dien-1-yl)(cyclopenta-2, 4-dien-1-yl)iron (HL 2 ). Complexes were designed, synthesized, and characterized using various spectroscopic techniques. Molar conductance data exposed that the complexes were electrolytes except La(III)-HL 2 complex, which was non-electrolyte. IR spectra denoted that Schiff bases were coordinated with transition metal ions in a bidentate manner, N, N donor sites with L 1 and N, O donor sites with HL 2 . All complexes were octahedral and prepared in a 1:1 molar ratio with the ligands. Thermal behavior of the complexes was studied. The in vitro antibacterial activities of these compounds were evaluated against eight bacterial species such as four Gram positive bacteria ( Staphylococcus aureus, Bacillus cereus, Bacillus subtilis, Streptococcus faecalis), and four Gram negative bacteria ( Escherichia coli, Pseudomonas aeruginosa, Neisseria gonorrhoeae, Salmonella typhimurium ) and results displayed that title compounds are biologically active. Also, they were assessed for their anticancer activities against cell line MCF-7 for breast cancer. Finally, molecular docking studies were tested for all prepared compounds with two different COVID-19 receptors (7BZ5 and 7C8J), also, against 3HB5 receptor of breast cancer. Molecular docking has shown favorable interaction between the title compounds and three protein receptors. This paper affords a manifestation of a novel tradition by which Comments on Inorganic Chemistry starts publishing original research content that, nonetheless, preserves the Journal's identity as a niche for a critical discussion of contemporary literature in inorganic chemistry; for previous manifestations, see Comments Inorg. Chem . 2020, 40, 277–303, and references cited in the abstract thereof. GRAPHICAL ABSTRACT: uf0001